HUBUNGAN Hubungan Media Adobe Flash terhadap Pembelajaran Fiqih melalui Motivasi Belajar Siswa MAN Kota Blitar - Miftakhul rohman; moh mirwan hariri (Universitas Nahdlatul Ulama Blitar, 2021)
Based on preliminary observation note that, in learning activities, teachers deliver materials with power point media less attract students to be active, this is seen only passive students in learning activities. Such activities make students less motivated. The purpose of this study is 1) Describe the implementation of student learning jurisprudence through the application of Adobe Flash media. 2) Describe the learning activities of jurisprudence students through the application of Adobe Flash media. 3) Describing the results of study of jurisprudence of students of Blitar City through the application of Adobe Flash media on basic competence “Explaining the provisions of inheritance law in Islam.” Based on the results of research can be concluded that the application of Adobe Flash media can improve the activity and learning outcomes of students, apply and develop Adobe Flash media in learning jurisprudence with material Explain the provisions of inheritance law in Islam more deepened.